Cutis 2020
DOI: 10.12788/cutis.0077
|View full text |Cite
|
Sign up to set email alerts
|

Update on Pediatric Atopic Dermatitis

Abstract: WWW.MDEDGE.COM/DERMATOLOGY CLINICAL REVIEW Recent studies have led to new insights into atopic dermatitis (AD) pathogenesis and epidemiology as well as its impact on the quality of life of affected children and adolescents. In addition, there are several novel topical and systemic agents recently approved and in late-stage clinical development programs. Epidemiologic insights include relative prevalence rates in different countries and studies of subsets of pediatric patients with different disease longevity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 25 publications
0
15
0
Order By: Relevance
“…Similarly, a questionnaire-based survey of 91,642 children in the United States between the ages of 0 and 17 years found that children with AD had a higher chance of experiencing four or more nights of impaired sleep per year [1,41]. This effect was even more pronounced in children with severe AD than in those with mild or moderate AD [1,41].…”
Section: Burden Of Atopic Dermatitis (Ad)mentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, a questionnaire-based survey of 91,642 children in the United States between the ages of 0 and 17 years found that children with AD had a higher chance of experiencing four or more nights of impaired sleep per year [1,41]. This effect was even more pronounced in children with severe AD than in those with mild or moderate AD [1,41].…”
Section: Burden Of Atopic Dermatitis (Ad)mentioning
confidence: 98%
“…In a longitudinal cohort study following 13,988 children in the United Kingdom from the ages of 2 to 16 years, it was found that children with any form of AD, even mild or inactive AD, had statistically significantly increased odds of poor sleep quality, and that children with active AD were almost 50% more likely to encounter increased disturbances to their sleep throughout childhood [40]. Similarly, a questionnaire-based survey of 91,642 children in the United States between the ages of 0 and 17 years found that children with AD had a higher chance of experiencing four or more nights of impaired sleep per year [1,41]. This effect was even more pronounced in children with severe AD than in those with mild or moderate AD [1,41].…”
Section: Burden Of Atopic Dermatitis (Ad)mentioning
confidence: 99%
“…AD flares also exacerbate negative impact on sleep [ 2 , 5 ]. A USA-based survey of more than 90,000 children aged 0–17 years revealed that children who reported having AD within the past year had a higher chance of experiencing impaired sleep, and children with severe AD reported more instances of sleep disruption than children with mild or moderate AD [ 5 , 6 ]. Similarly, a cohort study of almost 14,000 British children aged 2–16 years found that children with AD, even those with cases of mild or inactive disease, had significantly worse sleep quality relative to children without AD [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 , 4 , 5 ]. Its onset is usually concentrated in early childhood, but 2–10% of adults have AD, leading to a significant decrease in quality of life and increased psychological burdens [ 6 , 7 , 8 , 9 ]. The factors causing AD are not clear at present, but are mainly attributed to filaggrin (FLG), resulting in impaired skin barrier function [ 10 ] and changes in immune system function [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%